PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN METODE EKSPERIMEN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA-FISIKA SISWA KELAS VIII.A SMPN 12 KOTA BENGKULU - Dedy Hamdani; Dio Aru Prasetya; Connie Connie (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to improve the activity and learning outcomes of students with the implementation of problem-based learning (PBL) model. The subjects were the students of class VIII.A of state junior high school 12 (SMPN 12) of city of Bengkulu as many as 24 students. Data obtained from the test and observations sheets were analyzed using descriptive statistics. This research was conducted in four phases: planning, action, observation, and reflection. The results showed that the learning activities of students in the first cycle with an average score of 25.5 in enough categories, the second cycle of 33.5 in good categories, and the third cycle of 37.5 in good categories. The learning outcomes of students obtained for the cognitive aspects of the first cycle are the average values ​​of 67.75 and 62.50% of mastery learning; the second cycle are the average values ​​of 82.88 and 95.83% of mastery learning; and the third cycle are the average values ​​of 76.03 and 87.50% of passing grade. Learning outcomes of students ​​obtained for the affective aspects of the first cycle by an average of 57.64; the second cycle of 73.07; and the third cycle of 76.74. Learning outcomes of students obtained for psychomotor aspects of the first cycle values ​​ by an average of 74.65; the second cycle of 94.97; and the third cycle of 96.01. In general it can be said that the implementation of problem based learning model with the experimental method can increase the activity and learning outcomes of students. Keywords: activity learning, experimental methods, learning outcomes, problem based learning model.